Contribuições decolonais e feministas ao debate geográfico sobre corpo e território: mulheres da Terra Indígena Kaxarari e Rio Guaporé e a defesa do corpo-território - Hellen Virginia da Silva Alves (Confins)
This study presents the main contributions of Latin American decolonial and feminist thinking to geographic studies on body-territory. The research was carried out in the light of the phenomenological method. Through field research, it was verified the relational praxis between the bodies of women living in the Kaxarari and Rio Guaporé Indigenous Lands and the territory. It was found that the decolonial and feminist thoughts found valuable sources in both the worldview and the historical resistance of Aboriginal peoples to colonialism and coloniality. These sources contributed to the updating of the geographical concept of territory, which was previously based exclusively on Eurocentric standards. The main responsible for the extension/modernization of the geographic look on the body and the territory were Latin American Indigenous women and feminists, as they brought the interrelationship between body-territory-land to the center of the geographic and political debate, expanding the scales of analysis and the meanings of these categories. For them, the material and immaterial relations that the bodies maintain with the territory (and their worlds) ensure the existence of the collective in conditions of dignity, which is why the defense of the territory becomes a defense of the very life of the collective body.